International Students' Adjustment Towards Implementing Indonesian Language in Communication - Marsevani, Maya; Satrio, Abdul Aziz; Az zahra, Amanda; Teresa, Amelia; Sayow, Eirene Lady Marchela; Darsono, Elsha Ridzky Fadila; Fitriana, Nur; Selinna, Selinna (English Language Education, Universitas Internasional Batam, 2024)
Adjustment to the Indonesian language is a popular issue for international students while studying abroad in Indonesia. This research aims to analyze the ability as well as displaying the point of view of international students in implementing Indonesian language in communication highlighting what are the confusion and shocks from many aspects that they experienced during adjustment of communicating in Indonesia. As how mankind socializes one another through communication, direct or indirect, language is the tool to support communication between two or more people. In this case, Indonesian language as a communication tool exists among many other languages and globally spread its wings not only as a conversation support between two or more people, but also as a language that is learned by people from various backgrounds through a mandatory program of Indonesian for foreign speakers (BIPA). To communicate, adjustment is highly needed, especially to speak Indonesian language as a foreign language.